Maoism a global history - Julia Lovell (New York Knopf, 2019)
"Since the heyday of Mao Zedong, there has never been a more crucial time to understand Maosim. Although to Western eyes it seems that China has long abandoned the utopian turmoil of Maoism in favour of authoritarian capitalism, Mao and his ideas remain central to the People' Republic and the legitimacy of its communist government. As disagreements and conflicts between China and the West are likely to mount, the need to understand the political legacy of Mao will only become more urgent. Yet during Mao's lifetime and beyond, the power and appeal of Maoism has always extended beyond China. Across the globe, Maoism was a crucial motor of the Cold War: it shaped the course of the Vietnam War (and the international youth rebellion it triggered) and brought to power the murderous Khmer Rouge in Cambodia; it aided, and sometimes handed victory to, anti-colonial resistance movements in Africa; it inspired terrorism in Germany and Italy, and wars and insurgencies in Peru, India and Nepal, some of which are still with us today - more than forty years after the death of Mao. In this new history, acclaimed historian Julia Lovell revaluates Maoism, analysing both China's engagement with the movement and its legacy on a global canvas. It's a story that takes us from the tea plantations of north India to the sierras of the Andes, from Paris's 5th Arrondissement to the fields of Tanzania, from the rice paddies of Cambodia to the terraces of Brixton. Starting from the movement's birth in northwest China in the 1930s and unfolding right up to its present-day violent rebirth, this is the definitive history of global Maoism"-- Provided by publisher.
Includes index
Keywords: Mao, Zedong, 1893-1976.